Embodying pain : an exegesis presented in partial fulfillment of the requirements for the postgraduate degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Martin, Somn (Massey University, 2024)
Art provides a unique ability to attempt to communicate the experience of pain to others. I am compelled to study pain in order to understand myself, others, and the world at large. I am compelled to create art on the subject of pain to share this understanding with others. My art practice has several elements. I create figural sculptures of bodies in pain made out of clay stoneware and glaze or treat them with iron oxide. These figures are then arranged in environments with lightly rusted steel box frame structures, cotton cord, and wood. Sometimes the sculptural assemblages cast large elongated shadows made from sumi ink or charcoal.
Figure 8 is reproduced with permission.
Keywords: 360602 Fine arts